The Status of English in the European Union after Brexit - Skorupa-Wulczyńska, Aneta (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2023)
The aims of the article are to analyse the legal status of English after Brexit and present possible scenarios for this language in the post-Brexit Union. Firstly, the article highlights the status of languages in the EU and depicts three major categories of languages in the EU: Treaty languages, official and working languages. Secondly, the article analyses two possible scenarios for retaining the official and working status of English through notifications by Ireland and Malta. Thirdly, the paper focuses on the third scenario of introducing English as a single EU official language. Finally, the article outlines the status quo of English in the EU after UK’s withdrawal from the EU. It concludes that English is likely to remain the official and working language of the EU as a result of proper notification made by either Ireland or Malta.